(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The persistent and accelerating impacts of climate change present substantial challenges to the hydrological systems of Central Asia, particularly for Uzbekistan, where river-dependent water management and hydraulic infrastructures are integral to national sustainability, food security, and socioeconomic stability. This article investigates the current and projected impacts of climate change on the stability of hydraulic structures in Uzbekistan’s river basins, synthesizing global and regional climate projections, hydrological data, and engineering analyses. A systematic review and original data assessment are used to identify vulnerabilities and develop evidence-based adaptation strategies aimed at reinforcing the resilience of dams, weirs, diversion canals, and other critical water control structures. The findings highlight the urgent need for modernization, proactive risk assessment, and integrated water resource management. The study concludes with recommendations for policymakers, engineers, and researchers to ensure the long-term functionality and safety of hydraulic infrastructure in Uzbekistan under increasingly volatile climatic conditions.